Ocorrência de cisticercose em bovinos na região oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2012)
The Bovine cysticercosis is a parasitic zoonosis caused by the larval stage of taenia saginata that is detrimental to the productive chain of the beef and represents a major public health problem. It is considered a zoonosis endemic occurring mainly in rural areas of developing countries. Its occurrence is related to the precarious sanitary conditions and low socioeconomic and cultural level of the population. Control of the disease is based on the set of preventive measures designed to break the cycle of this parasite, taking the meat inspection in slaughterhouses an important tool. This study aimed to evaluate the occurrence of cysticercosis in 11 cities from the region west of Rio Grande do Sul, in the period between January 2010 and December 2011. From a total of 243,274 cattle in a slaughterhouse inspected under federal inspection in the city of Alegrete / RS, 158,154 were from the Alegrete, Barra do Quaraí, Itacurubi, Itaqui Maçambará, Manoel Viana, Quaraí, Rosario do Sul, the Santana Livramento, São Borja and Uruguaiana. We diagnosed 9,592 cases of cysticercosis in animals from these municipalities. Having an occurrence of 6.0% over the number of animals slaughtered. Cases diagnosed 3037 and 6555 living cysts were calcified cysts accounting for 31.7% and 68.3%, respectively. It has been found the occurrence of bovine cysticercosis in all cities analyzed, with the same variation between 3.7% to 10.6%, demonstrating the endemic situation of the disease in the region.
Keywords: Cisticercose bovina; Taenia Saginata; Zoonose; Bovine cysticercosis; Zoonosis; CNPQ::CIENCIAS AGRARIAS